Digital Marketing Study, Through Instagram Media Case Study of Private Universities in the Tangerang Region - Indra Gunawan; Tjong Se Fung; Diana Silaswara (Fakultas Bisnis, 2020)
The rapid development of technology makes a big change to every activity carried out both individuals and organizations. The speed of information is a necessity for every individual and organization. Universities as institutions engaged in education make changes in communication to the community. In implementing the tri dharma of tertiary institutions in each of their activities, the tertiary institution utilizes social media. One of the social media chosen is Instagram because it is loved by millennials. The use of Instagram as a medium of communication has an impact on increasingly creative tertiary institutions conducting information on each of their activities. With the use of social media, tertiary institutions can inform the public about their creativity so that it impacts on public confidence in their learning activities